Ent-Kaurene diterpenoids from Isodon phyllostachys. Issue 4 (25th January 2017) - Yang, Jin; Wang, Wei-Guang; Wu, Hai-Yan; Liu, Miao; Jiang, Hua-Yi; Du, Xue; Li, Yan; Pu, Jian-Xin; Sun, Han-Dong
Graphical abstract: Highlights: Four new ent -kaurene diterpenoids have been isolated from Isodon phyllostachys . Compound1 features a novel dihydro-2 H -pyran ring motif. Compounds2 and3 bear a rare 20-nor- ent -kaurene structure. Compound4 possesses a rare 7, 20-cyclo- ent -kaurene skeleton. Abstract: Four new ent -kaurene diterpenoids, phyllostachysins M–P (1 –4 ) have been isolated from the aerial parts of Isodon phyllostachys . Compound1 features a novel dihydro-2 H -pyran ring motif, which was formed by an unusual cleavage in ring-A.2 and3 bear a rare 20-nor- ent -kaurene structure, but4 has a rare 7, 20-cyclo- ent -kaurene skeleton. Their structures were elucidated on the basis of extensive spectroscopic analyses. Compounds1, 3, and4 were evaluated for their cytotoxic activity against five human tumor cell lines.